0
$\begingroup$

I am reading Quantum Field Theory in Condensed Matter Physics by A.M. Tsvelik. In Chapter 20, it is claimed that introducing three Majorana fermions $\gamma^\mu_i$ on each site $i$ of the lattice (such that $\{\gamma^\mu_i,\gamma^\nu_j\}=\delta^{\mu,\nu}\delta_{i,j}$), spin-$1/2$ operators can be expressed as $$S_i^\lambda=-{i\over 2}\epsilon_{\lambda\mu\nu} \gamma_i^\mu\gamma_i^\nu$$ I am trying to show the commutations relations $$[S_i^\lambda,S_j^\rho]=i\epsilon_{\lambda\rho\sigma}S^\sigma_i \delta_{i,j}$$ Unfortunately, my calculation is wrong (by a factor 2). I would be very grateful if somebody could find the mistake.

I start with $$[S_i^\lambda,S_j^\rho] =-{1\over 4}\epsilon_{\lambda\mu\nu}\epsilon_{\rho\zeta\xi} \big(\gamma_i^\mu\gamma_i^\nu\gamma_j^\zeta\gamma_j^\xi -\gamma_j^\zeta\gamma_j^\xi\gamma_i^\mu\gamma_i^\nu\big)$$ Using the anti-commutation relations between Majorana, I get $$\eqalign{ \gamma_j^\zeta\gamma_j^\xi\gamma_i^\mu\gamma_i^\nu &=\gamma_j^\zeta\big(\delta^{\xi,\mu}\delta_{i,j} -\gamma_i^\mu\gamma_j^\xi\big)\gamma_i^\nu \cr &=\delta^{\xi,\mu}\delta_{i,j}\gamma_j^\zeta\gamma_i^\nu -\big(\delta^{\mu,\zeta}\delta_{i,j}-\gamma_i^\mu\gamma_j^\zeta\big) \big(\delta^{\nu,\xi}\delta_{i,j}-\gamma_i^\nu\gamma_j^\xi\big)\cr &=\delta^{\xi,\mu}\delta_{i,j}\gamma_j^\zeta\gamma_i^\nu +\delta^{\mu,\zeta}\delta_{i,j}\gamma_i^\nu\gamma_j^\xi +\delta^{\nu,\xi}\delta_{i,j}\gamma_i^\mu\gamma_j^\zeta -\gamma_i^\mu\gamma_j^\zeta\gamma_i^\nu\gamma_j^\xi -\delta^{\mu,\zeta}\delta^{\nu,\xi}\delta_{i,j} \cr &=\big(\delta^{\xi,\mu}\gamma_j^\zeta\gamma_i^\nu \!+\!\delta^{\mu,\zeta}\gamma_i^\nu\gamma_j^\xi \!+\!\delta^{\nu,\xi}\gamma_i^\mu\gamma_j^\zeta\big)\delta_{i,j} -\gamma_i^\mu\big(\delta^{\nu,\zeta}\delta_{i,j} -\gamma_i^\nu\gamma_j^\zeta\big)\gamma_j^\xi -\delta^{\mu,\zeta}\delta^{\nu,\xi}\delta_{i,j} \cr &=\big(\delta^{\xi,\mu}\gamma_j^\zeta\gamma_i^\nu +\delta^{\mu,\zeta}\gamma_i^\nu\gamma_j^\xi +\delta^{\nu,\xi}\gamma_i^\mu\gamma_j^\zeta -\delta^{\nu,\zeta}\gamma_i^\mu\gamma_j^\xi\big) +\gamma_i^\mu\gamma_i^\nu\gamma_j^\zeta\gamma_j^\xi -\delta^{\mu,\zeta}\delta^{\nu,\xi}\delta_{i,j} \cr }$$ so that the commutator reads $$[\gamma_i^\mu\gamma_i^\nu,\gamma_j^\zeta\gamma_j^\xi] =-\big(\delta^{\xi,\mu}\gamma_j^\zeta\gamma_i^\nu +\delta^{\mu,\zeta}\gamma_i^\nu\gamma_j^\xi +\delta^{\nu,\xi}\gamma_i^\mu\gamma_j^\zeta -\delta^{\nu,\zeta}\gamma_i^\mu\gamma_j^\xi\big) +\delta^{\mu,\zeta}\delta^{\nu,\xi}\delta_{i,j}$$ Since $(\gamma_i^\mu)^2=1/2$ for Majorana fermions, $$\eqalign{ \epsilon_{\lambda\mu\nu}\epsilon_{\rho\zeta\xi} \delta^{\xi,\mu}\gamma_i^\zeta\gamma_i^\nu &=-\epsilon_{\lambda\nu\mu}\epsilon_{\rho\zeta\mu}\gamma_i^\zeta\gamma_i^\nu\cr &=-\big(\delta^{\lambda,\rho}\delta^{\nu,\zeta} -\delta^{\lambda,\zeta}\delta^{\nu,\rho}\big)\gamma_i^\zeta\gamma_i^\nu\cr &=-\delta^{\lambda,\rho}\big(\gamma_i^\zeta\big)^2 +\gamma_i^\lambda\gamma_i^\rho \cr &=-{3\over 2}\delta^{\lambda,\rho}+\gamma_i^\lambda\gamma_i^\rho \cr }$$ because of the implicit sum over $\zeta$ in the first term. Similarly, $$\eqalign{ &\epsilon_{\lambda\mu\nu}\epsilon_{\rho\zeta\xi} \delta^{\mu,\zeta}\gamma_i^\nu\gamma_j^\xi ={3\over 2}\delta^{\lambda,\rho}-\gamma_i^\rho\gamma_i^\lambda\cr &\epsilon_{\lambda\mu\nu}\epsilon_{\rho\zeta\xi} \delta^{\nu,\xi}\gamma_i^\mu\gamma_j^\zeta ={3\over 2}\delta^{\lambda,\rho}-\gamma_i^\rho\gamma_i^\lambda\cr &\epsilon_{\lambda\mu\nu}\epsilon_{\rho\zeta\xi} \delta^{\nu,\zeta}\gamma_i^\mu\gamma_j^\xi =-{3\over 2}\delta^{\lambda,\rho}+\gamma_i^\rho\gamma_i^\lambda\cr }$$ so that $$\eqalign{ \delta^{\xi,\mu}\gamma_j^\zeta\gamma_i^\nu +\delta^{\mu,\zeta}\gamma_i^\nu\gamma_j^\xi +\delta^{\nu,\xi}\gamma_i^\mu\gamma_j^\zeta -\delta^{\nu,\zeta}\gamma_i^\mu\gamma_j^\xi &=3\delta^{\lambda,\rho}+\gamma_i^\lambda\gamma_i^\rho -3\gamma_i^\rho\gamma_i^\lambda\cr &=3\delta^{\lambda,\rho}+\gamma_i^\lambda\gamma_i^\rho -3\big(\delta^{\lambda,\rho}-\gamma_i^\lambda\gamma_i^\rho\big)\cr &=4\gamma_i^\lambda\gamma_i^\rho\cr }$$ The last term of the commutator is $$\epsilon_{\lambda\mu\nu}\epsilon_{\rho\zeta\xi} \delta^{\mu,\zeta}\delta^{\nu,\xi} =\epsilon_{\lambda\mu\nu}\epsilon_{\rho\mu\nu} =\delta^{\lambda,\rho}$$ so $$\eqalign{ [S_i^\lambda,S_j^\rho] &={1\over 4}\big(4\gamma_i^\lambda\gamma_i^\rho -\delta^{\lambda,\rho}\big)\delta_{i,j} \cr }$$ This result is unfortunately wrong! I expect instead $$\eqalign{ i\epsilon_{\lambda\rho\sigma}S_i^\sigma &={1\over 2}\epsilon_{\lambda\rho\sigma} \epsilon_{\sigma\zeta\xi} \gamma_i^\zeta\gamma_i^\xi\cr &={1\over 2}\epsilon_{\lambda\rho\sigma} \epsilon_{\zeta\xi\sigma} \gamma_i^\zeta\gamma_i^\xi\cr &={1\over 2}\big(\gamma_i^\lambda\gamma_i^\rho -\gamma_i^\rho\gamma_i^\lambda\big) \cr &={1\over 2}\big(2\gamma_i^\lambda\gamma_i^\rho-\delta^{\lambda,\rho}\big) }$$

$\endgroup$
1
$\begingroup$

When you dealt with the last term, product of deltas, you missed a factor of two: \begin{equation} \epsilon_{\lambda\mu\nu} \epsilon_{\rho\mu\nu} = {\color{red}2}\delta^{\lambda,\rho} \end{equation}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.